Pengaruh Influencer Marketing dan Media Sosial Marketing terhadap Keputusan Menabung di Bank Syariah Indonesia Brand Awareness sebagai Variabel Moderating - Syawaruddin Syawaruddin; Sudirman Sudirman; Samsul Arifai (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of influencer marketing and social media marketing on saving decisions at Bank Syariah Indonesia (BSI) KCP Makassar Veteran, with brand awareness as a moderating variable. The research is motivated by the increasing use of social media as a medium of promotion and communication between financial institutions and the public, particularly in introducing products based on sharia principles. The study employed a quantitative approach with an associative research design, in which data were collected through questionnaires distributed to 200 active customers of BSI KCP Makassar Veteran. Data were analyzed using SPSS version 26 through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA). The results indicate that influencer marketing has a positive but insignificant effect on saving decisions, while social media marketing has a positive and significant effect. Moreover, brand awareness was found to moderate the relationship between social media marketing and saving decisions, but not between influencer marketing and saving decisions. These findings highlight that the effectiveness of BSI’s digital marketing strategies largely depends on the strength of social media engagement and brand awareness in building trust and encouraging customers to save in Islamic financial institutions.